Modeling of thermo-electric battery’s calculation of hydrocarbons recuperation system - Boichenko, S. V.; Ivanov, S. V. (Proceedings of National Aviation University (archive), 2003)
With the maintainability to insure effective work of breathing valve of new generation authors developed thermal model expectation of a design thermo-electric battery, which in some measure of approach describes process of fuel condensation